2013 IEEE Power &Amp; Energy Society General Meeting 2013
DOI: 10.1109/pesmg.2013.6672438
|View full text |Cite
|
Sign up to set email alerts
|

Wave height forecasting to improve off-shore access and maintenance scheduling

Abstract: Abstract-This paper presents research into modelling and predicting wave heights based on historical data. Wave height is one of the key criteria for allowing access to off-shore wind turbines for maintenance. Better tools for predicting wave height will allow more accurate identification of suitable "weather windows" in which access vessels can be dispatched to site. This in turn improves the ability to schedule maintenance, reducing costs related to vessel dispatch and recall due to unexpected wave patterns.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…The training set was limited to 2 years of data (2006 and 2007), while the test set was from 00:00 1 January 2008 until the end of the data set. An earlier study showed that varying the length of the training set had no significant impact on model accuracy for this data …”
Section: Methodologiesmentioning
confidence: 84%
See 1 more Smart Citation
“…The training set was limited to 2 years of data (2006 and 2007), while the test set was from 00:00 1 January 2008 until the end of the data set. An earlier study showed that varying the length of the training set had no significant impact on model accuracy for this data …”
Section: Methodologiesmentioning
confidence: 84%
“…The ANN is perhaps the most commonly applied intelligent system technique for nonlinear regression problems and has in the past been applied to wave height modeling . The attraction of an ANN is that with a three‐layer network comprised of simple units (neurons), any function can be approximated .…”
Section: Methodologiesmentioning
confidence: 99%
“…and wind speed determine whether it is possible to perform maintenance activities at sea since the vessels access to offshore turbines are limited in by these factors. For example, [8] presents operational wave height limits for various forms of transportation, including helicopters and sea vessels to improve the ability to schedule maintenance, reducing costs related to vessel dispatch and recall due to unexpected wave patterns. Catterson et al (2016), [9], proposed an economic forecasting metric (EFM) which considers the economic impact of an incorrect forecast above or below critical wave height boundaries.…”
Section: Related Work Of Forecasting Using Data-driven Methodsmentioning
confidence: 99%
“…Lost turbine availability is related to the failure of a component, but also depends largely on access to the turbine, and in [125], a computational approach based on probability calculations is developed, allowing estimates to be made on very fast offshore access probabilities and expected delays. Furthermore, Dinwoodie et al [126] performed research on the modeling and prediction of wave height, which is one of the key criteria for access to offshore wind farms, and this was done through data mining.…”
Section: Maintenance Optimization (M_opt)mentioning
confidence: 99%